L’EAU EST TOUJOURS VITALE,PARFOIS DESTRUCRTICE! - Snouci, Bouasria; Mederbal, K; Khaldi, A (European Scientific Journal, ESJ, 2013)
In this article we highlight the usefulness of water for people and their environments. It is the driving force of all life on earth, but can also become part of nuisance if it is misused or misdirected in its movement. It sometimes becomes angry and destructive.